The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.02.24.23285761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral CBD treatment is associated with an anti-inflammatory gene expression signature in myeloid cells of people living with HIV

Abstract: HIV-related comorbidities appear to be related to chronic inflammation, a condition characterizing people living with HIV (PLWH). Prior work indicates that cannabidiol (CBD) might reduce inflammation; however, the genetics underpinning this effect are not well investigated. Our main objective is to detect gene expression alterations in human peripheral blood mononuclear cells (PBMCs) from PLWH after at least one month of CBD treatment. We collected PBMCs from three HIV-positive subjects at baseline and after C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…One RCT observed that 12 weeks of 400–800 mg/day of CBD reduced concentrations of IL-6 in adults diagnosed with cocaine use disorder [ 28 ]. Additionally, another study observed that 3 weeks of 67 mg/day of CBD oil was associated with decreased expression of proinflammatory genes and reductions in C -reactive protein (CRP) in human immunodeficiency virus (HIV)-positive participants [ 29 ]. Conversely, another RCT observed no effect on IL-6 and CRP after 13 weeks of 200 mg/day of CBD in adults with type 2 diabetes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…One RCT observed that 12 weeks of 400–800 mg/day of CBD reduced concentrations of IL-6 in adults diagnosed with cocaine use disorder [ 28 ]. Additionally, another study observed that 3 weeks of 67 mg/day of CBD oil was associated with decreased expression of proinflammatory genes and reductions in C -reactive protein (CRP) in human immunodeficiency virus (HIV)-positive participants [ 29 ]. Conversely, another RCT observed no effect on IL-6 and CRP after 13 weeks of 200 mg/day of CBD in adults with type 2 diabetes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%